The Effect of Strawberry (Fragaria x ananassa) Fruit Juice on Renal Cell Histological Damage of Mice Induced by Rhodamine B - Najmi, Dea Saufika; Suparyanti, Endang Listyaningsih; Sari, Yulia (Nexus Biomedika, 2015)
Background:Strawberry (Fragaria x ananassa) contains many antioxidant phytochemicals such as vitamin C, anthocyanins and ellagic acid that may exhibit significant protection of kidney cells from free radicals. In present study, Strawberry (Fragaria x ananassa) fruit juice was evaluated for its nephroprotector effect on mice renal damage induced by Rhodamine B. Methods:This research was an experimental laboratory study with the posttest only controlled group design. Samples were 28 male mice, Swiss webster type, 2-3 months old and Â± 20 g of each weight. Samples were divided into 4 groups of 7 mice each. This research used consecutive sampling. Strawberry juice was given for 16 days in a row, while Rhodamine B (0.2 ml/20 gr of mice body weight) was given on 10th to 16th day. Negative Control Group (KK-) was given distilled water only. Positive Control Group (KK+) was given Rhodamine B. First Treatmennt Group (KP1) and Second Treatment Group (KP2) wereÂ  given 0.4 ml and 0.8 ml of Strawberry fruit juice per 20 gr of mice body weight and Rhodamine B. On the 17th day, mice were sacrificed by neck dislocation. After that, the kidney was dissected out and made for preparation with paraffin block method and stained with Hematoxilin Eosin (HE). The score of renal cells damage was determined by pyknosis, karyorrhexis, and karyolysis. The data were analyzed with One-Way ANOVA test (Î± = 0.05) and Least Significant Differences (LSD) test (Î± = 0.05). Results:The result of One-Way ANOVA test showed that there was a significant difference in score of renal cells (p < 0.05). LSD test showed a significant difference in score of renal cells (p < 0.05) across all pair groups. Conclusions:Strawberry (Fragaria x ananassa) fruit juice showed nephroprotector effect against renal cell histological damage in mice induced by Rhodamine B. Keywords:Strawberry fruit juice, Rhodamine B, renal cell histological damage.